Current state of leadless pacemakers: state of the art review. (3rd October 2019) - Afzal, Muhammad R.; Shah, Nupur; Daoud, Georges; Houmsse, Mahmoud
ABSTRACT: Introduction : Leadless pacemakers (LPs) are the latest advancement in the field of pacing. Experience from pivotal trials and post-marketing studies has proven the feasibility and safety of these devices. The LPs obviate the need of pulse generator pocket and leads, which translates into lower incidence of lead related complications and pocket related infections. This review will summarize the existing literature on the LPs, specifically indications; implant procedure, unique situations and long- term follow up. Areas covered : This review will summarize the results of published pivotal trials. Several multicenter studies where LP was used in the unique situations such as during concomitant AV node ablation and across bioprosthetic valve will also be discussed. An extensive search using PUBMED was performed to identify the relevant articles. Expert commentary : The use of LPs is expanding and the published results a preferential use of such devices for patients who need single ventricle pacing. Additionally, the use of these devices in several unique situations such as patients with inferior vena cava filters, bioprosthetic tricuspid valves and concomitant atrio-ventricular nodal (AV) ablation has also been shown to be safe.